2015
DOI: 10.1007/s00441-015-2249-x
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics of post-translational modifications of mammalian spermatozoa

Abstract: It is hard to fathom that one of the most highly differentiated cells in the body, the spermatozoon, spends over half of its developmental life without the capacity for nuclear protein biosynthesis. This is even more incredible when considering that protein synthesis is switched off long before the sperm is mature. As such, in order to obtain full functionality, spermatozoa rely on post-translational modifications (PTM) of existing proteins. Many PTM have been shown to play a role in the development of a sperm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 89 publications
0
50
0
Order By: Relevance
“…This converts ATP to cAMP [16]. The cyclic nucleotide then dissociates the sperm-specific PKA regulatory subunits from the catalytic subunits [114]. Further study reveals that the phosphorylation of tyrosine is altered in sAC Null Sperm.…”
Section: Ions Molecules and Reactive Oxygen Species Affect Capacitationmentioning
confidence: 99%
“…This converts ATP to cAMP [16]. The cyclic nucleotide then dissociates the sperm-specific PKA regulatory subunits from the catalytic subunits [114]. Further study reveals that the phosphorylation of tyrosine is altered in sAC Null Sperm.…”
Section: Ions Molecules and Reactive Oxygen Species Affect Capacitationmentioning
confidence: 99%
“…These can be supplemented with gene ontology databases and analysis resources for annotation, visualization, and integrated discovery (DAVID; Huang, Sherman, & Lempicki, ) and protein analysis through evolutionary relationships (PANTHER; Thomas et al, ) classification systems, search tools for the retrieval of interacting genes/proteins (STRING): functional protein association networks (Jensen et al, ). In concert, they have helped to define biological significance, molecular functionality, cellular compartment, and pathways advancing our understanding of the cascade of events associated with immune regulatory molecules and their modifications that alter the fertility status of the individual (Baker, ). For example, ASA antigens listed in Table subjected to STRING protein‐interaction analysis revealed 88 different significant functional reproductive biological processes (Supplementary Data 1).…”
Section: Diagnostic Methods To Identify Immune Regulatory Moleculesmentioning
confidence: 99%
“…Traditional whole‐sperm proteomic approaches such as 2D polyacrylamide gel electrophoresis, mass spectrometry (MS) and differential in‐gel electrophoresis have allowed for the identification of numerous sperm‐specific proteins (Agarwal et al., ; du Plessis, Kashou, Benjamin, Yadav, & Agarwal, ). Studies of the sperm proteome have demonstrated how post‐translational modifications such as phosphorylation, glycosylation, proteolytic cleavage and mutation bring about physiological changes in spermatozoa function (Aitken & Baker, ; Baker, ). Furthermore, proteomic analysis has allowed for the study of spermatozoa in different functional states, for example immature vs. mature, uncapacitated vs. capacitated, normal vs. defective, all of which impact the reproductive potential of the male (Agarwal, Durairajanayagam, Halabi, Peng, & Vazquez‐Levin, ; Barazani, Agarwal, & Sabanegh, ; Gupta, Ghulmiyyah, Sharma, Halabi, & Agarwal, ; du Plessis et al., ).…”
Section: Average Values Do Not Provide Accurate Information Of Sperm mentioning
confidence: 99%
“…Due to the silencing of nuclear transcription in ejaculated spermatozoa, post‐translational modifications of existing proteins are necessary for proper sperm function. These modifications include phosphorylation, glycosylation, disulphide cross‐linking, ubiquitination, acetylation and methylation (Baker, ).…”
Section: Single‐cell Analysis In Sperm Proteomics: Flow Cytometrymentioning
confidence: 99%